Mortuary and bioarchaeological perspectives in Bronze Age Arabia - Williams, Kimberly D.; Gregoricka, Lesley A.; Larsen, Clark Spencer (Bioarchaeological interpretations of the human past., 2019)
This volume brings together an international consortium of archaeologists and bioarchaeologists at the forefront of mortuary archaeology work across Arabia to examine continuity/change in death and remembrance. While mortuary archaeology and bioarchaeology contribute important perspectives to the interpretation of life/death in ancient Arabia, these subdisciplines are rarely brought together in this region, and only recently have skeletal remains been recognized as a rich source of scientific data complementing burial context. Such joint collaboration highlights the novel, interdisciplinary perspective proposed in this volume, resulting in a synthesis of new ideas and interpretations that will undoubtedly guide future archaeological endeavors in Arabia and beyond.